Building a pulmonary vascular service: the 12‐year experience and outcomes of the Auckland pulmonary arterial hypertension clinic. Issue 6 (9th June 2013) - Wasywich, C. A.; Cicovic, A.; McWilliams, T.; Coverdale, H. A.; Stewart, C.; Whyte, K.
Abstract Background and Aims Pulmonary arterial hypertension (PAH) is associated with significant morbidity and mortality. In New Zealand, access to PAH‐specific pharmacotherapy has been restricted for economic reasons. Since 2009, access to medication has been provided by a Special Authority scheme that ensures equity of access for all patients. Management of patients with PAH in this environment poses unique challenges. This study describes outcomes of patients managed in the Auckland PAH clinic over a 12‐year period. Methods The clinic database was interrogated. Patients were eligible for this study if they had PAH (World Health Organization (WHO) Class 1, 1′ and 4) and had been managed in the clinic from the year 2000. Results One hundred and twenty‐six patients (75% female, mean age at diagnosis 50) were included. Most had idiopathic PAH (37%) or PAH because of connective tissue disease (29%). At diagnosis, patients had advanced disease (median WHO Class III, 6‐min walk distance 367 m and pulmonary vascular resistance of 10.6 Wood Units). Initial therapy was sildenafil in most cases. PAH‐specific therapy was associated with improved WHO class and longer 6‐min walk distance (P < 0.01 for both). Thirty per cent of patients were escalated to combination therapy. Survival was 91% at 1 year and 67% at 5 years. Conclusions Despite historic difficulties with access to PAH‐specific therapy, these data confirm benefits of therapy (primarily sildenafil as first‐line treatment) for patients with PAH managed within the Auckland PAH clinic. Survival data are comparable with other reported cohorts.